Analyzing the Cognitive Approach of Nepali Youth Job Seekers towards Online Recruitment - Ghimire, Binod; Upadhyay, Jitendra; Joshi, Surendra Prasad; Subedi, Sugam; Karki, Prajwal (The Harvest, 2024)
This study explored the factors influencing job seekers’ behavioral intentions to use e-recruitment platforms in Nepal. The study examined the relationships between Performance expectancy, effort expectancy, subjective norms, objective norms, facilitating conditions, and behavioral intentions. A sample of 250 students from public and private colleges participated. Through descriptive and causal-comparative methodologies, significant correlations between the variables were revealed. Regression analysis highlighted the predictive ability of performance expectancy (= .296, p < .001) and subjective norms (= .485, p < .001). The findings underscore the importance of these factors in shaping job seekers’ intentions to use online recruitment. This study contributes valuable insights for practitioners and stakeholders in the online recruitment sector, guiding tailoring platforms to the preferences of Nepali job seekers.